Rapid stability-indicative turbidimetric assay to determine the potency of cefadroxil monohydrate capsules - Marco, Bianca Aparecida de [UNESP]; Nunes Salgado, Erida Regina [UNESP] (Royal Soc Chemistry, 2018)
Microbiological methods for the analysis of antimicrobials are indispensable to quality control processes, since they can provide important information about their biological activities, which physicochemical methods are not able to provide. The aim of this study was to develop and validate a microbiological method for the quantification of cefadroxil capsules by turbidimetry, as well as evaluate the ability of the method to determine the stability of the drug under degradation conditions, using Staphylococcus aureus as the test microorganism and brain heart infusion broth as the culture medium, in the 3 x 3 parallel line assay design. The validation parameters were in accordance with ICH guidelines and the method was shown to be linear, selective, precise, robust and accurate in a concentration range of 30 to 120 mu g mL(-1). The developed turbidimetric method is a valid, simple, fast and more economical alternative methodology for the routine quality control of cefadroxil in its pharmaceutical dosage form.